Meningkatkan Kemampuan Guru PAUD Dalam Merencanakan Pembelajaran Melalui Pelatihan In-House Training Di KB-Padilatul Jihad - Fitria Ulfah; Euis Siti Fatimah Zuhro (LP2M STAI Al-Musaddadiyah Garut, 2026)
Currently, there are still many early childhood education (PAUD) teachers, particularly in remote areas, who teach with limited knowledge and without clear guidelines or a solid foundation for planning lessons, teaching, and evaluating students, as is the case at Padilatul Jihad PAUD. These conditions prompted the conduct of a study titled “Enhancing Early Childhood Education Teachers’ Ability to Plan Lessons through In-House Training at Padilatul Jihad Preschool.” The low proficiency of teachers in developing lesson plans is characterized by the monotonous application of drilling methods and a lack of variety in learning activities, with most teachers focusing primarily on reading and counting. This study aims to improve the ability of Padilatul Jihad PAUD teachers to develop lesson plans using the Kemmis and Taggart classroom action research model. Data collection was conducted through observation, interviews, Focus Group Discussions (FGDs), and questionnaires, while data analysis utilized qualitative descriptive techniques. The results of the study indicate an improvement in teachers’ abilities of up to 78%, which falls into the “good” category, thereby proving that the In-House Training model is effective in enhancing teachers’ ability to plan lessons at Padilatul Jihad Early Childhood Education Center. Keywords: Pedagogical Competence, In-House Training, Lesson Planning